KECEMASAN SOSIAL DITINJAU DARI HARGA DIRI PADA REMAJA STATUS SOSIAL EKONOMI RENDAH - Deby Pratiwi; Rina Mirza; Mukhaira El Akmal (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to determine the relationship between self-esteem and social anxiety. The research subjects used in this study were adolescents with low socioeconomic status in Environment VIII Belawan I numbering 115 people. Data obtained from a scale to measure self-esteem and social anxiety. The calculation is done by conducting the analysis prerequisite test (assumption test) which consists of a normality test and a linearity test. Analysis of the data used is to use Product Moment correlation with the help of SPSS 17 for Windows. The results of data analysis showed a correlation coefficient of -0.595 and a significance value of 0.000 (p <0.05). The results of the analysis of these data indicate a negative relationship between self-esteem and social anxiety. The results of this study indicate that the contribution given variable self-esteem to anxiety is 35.5 percent, the remaining 64.5 percent is influenced by other factors not examined. From the results of this study it can be concluded that the research hypothesis, namely there is a negative relationship between self-esteem and social anxiety can be accepted. Keywords: Self-esteem, Social Anxiety